Detection of Alterations in the Gut Microbiota and Intestinal Permeability in Patients With Hashimoto Thyroiditis - Cayres, Leonardo César de Freitas; de Salis, Larissa Vedovato Vilela; Rodrigues, Guilherme Siqueira Pardo; Lengert, André van Helvoort; Biondi, Ana Paula Custódio; Sargentini, Larissa Donadel Barreto; Brisotti, João Luiz; Gomes, Eleni; de Oliveira, Gislane Lelis Vilela (Frontiers in Immunology, 2021)
The Hashimoto thyroiditis (HT) is the most common autoimmune disease worldwide, characterized by chronic inflammation and circulating autoantibodies against thyroid peroxidase and thyroglobulin. Patients require hormone replacement with oral levothyroxine, and if untreated, they can develop serious adverse health effects and ultimately death. There are evidences that intestinal dysbiosis, bacterial overgrowth, and increased intestinal permeability favor the HT development and a thyroid-gut axis had been proposed and it seems to impact our entire metabolism. Here, we evaluated alterations in the gut microbiota in Brazilian HT patients and correlated this data with dietary habits, clinical data, and systemic cytokines and zonulin concentrations. Stool samples from 40 HT patients and 53 controls were analyzed by real-time PCR, the serum cytokine levels were evaluated by flow cytometry, zonulin concentrations by ELISA, and the dietary habits were recorded by a food frequency questionnaire. We observed a significant increase (P<0.05) in the Bacteroides species and a decrease in Bifidobacterium in HT patients’ samples. In addition, Lactobacillus species were higher in patients without thyroid hormone replacement, compared with those that use oral levothyroxine. Regarding dietary habits, we demonstrated that there are significant differences in consumption of vegetables, fruits, animal-derived proteins, dairy products, saturated fats, and carbohydrates between patients and control group, and an inverse correlation between animal-derived protein and Bacteroides genus was detected. The microbiota modulation by diet directly influences on the inflammatory profile due to the generated microbiota metabolites and their direct or indirect action on immune cells in gut mucosa. Although there are no differences in systemic cytokines in our HT patients, we detected increased zonulin concentrations, suggesting a leaky gut in HT patients. These findings could help understand the HT development and progression, while further investigations to clarify the underlying mechanisms of the diet-microbiota-immune system axis are still needed.